Acts of Desertion: Abandonment and Renouncement at the Sonoran Borderzone. Issue 2 (30th September 2014) - Squire, Vicki
Abstract What are 'acts of desertion', how do they feature in contemporary border struggles, and what might an emphasis on such acts bring to the analysis of the politics of mobility? This article seeks to address these questions in the context of the Sonoran borderzone, which crosses Mexico and the US. It develops an analysis that sheds light on contemporary border struggles in terms that acknowledge both the intensity of security practices as well as the significance of migratory acts, without pre‐fixing the relation between the two. The analysis shows how 'acts of desertion' involve differentiated dynamics of abandonment and renouncement, which demand appreciation of the ambiguities of contemporary border struggles. As acts that variously involve a dynamics of refusal, the article argues that acts of desertion challenge the limits of liberal citizenship, without wholly transcending its limitations.